Polysemy of Terms in Computational Linguistics - Nigora Satibaldieva (Scientific Trends, 2024)
This article examines polysemy in computational linguistics, highlighting the challenges and opportunities it presents. Polysemy, where a word has multiple meanings, is central to natural language processing and reflects the richness of human communication. The paper explores various aspects of polysemy, including Word Sense Disambiguation (WSD), semantic networks, and the impact of language evolution. It references key works by Polshchykova on terminology consistency and by Haber and Poesio on the interdisciplinary nature of polysemy research. The study emphasizes the importance of understanding the nuanced meanings of polysemous words and the role of context in their interpretation. It also discusses the significance of standardizing terminology and the implications of polysemy in professional communication within computational linguistics. The article concludes that addressing polysemy requires sophisticated computational approaches and interdisciplinary collaboration to enhance clarity and understanding in the field.
Keywords: Polysemy; computational linguistics; word sense disambiguation (wsd); semantic networks; natural language processing (nlp); terminology standardization; hyper-hyponymic relations; language evolution.